A systematic review of the current interventions available to support children living with parental cancer. Issue 10 (October 2019) - Alexander, Elise; O'Connor, Moira; Rees, Clare; Halkett, Georgia
Highlights: Empirically supported interventions are limited. Evaluation studies are insufficiently conducted. Premature to say what works and what does not. More methodologically robust research studies are required. Theoretical model conceptualising how children are impacted would assist research. Abstract: Objective: Children living with parental cancer are vulnerable to distress and developmental disruption. This review aims to identify current interventions to support cancer patients' children and summarise how effective these are based on children's reports. Methods: Between 25 May 2015 and 6 August 2018, a broad search strategy was used to identify relevant references. Seven databases were searched, and grey literature was also vetted. This review was informed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and Cochrane guidelines. Results: Eight studies evaluating six interventions were retained. Research designs and interventions were heterogenous, and study quality was low. A limited number of significant results were reported by studies. These evidenced improvement for PTSD symptoms, emotional regulation, and depression. However, overall current interventions do not appear effective among patients' children. Conclusion: Despite encouraging preliminary findings, interventions do not yet adequately support cancer patients' children. There is a need for more tailored and targeted interventions. A theoretical model conceptualising the impact of parental cancer may assist this. Practice implications: Findings will assist future intervention research by promoting standardised levels of care among cancer patients' children, that is empirically supported, effective, and meets principles of non-maleficence.